Talar Body Fracture Treated by Hindfoot Endoscopic Reduction and Internal Fixation - Airi Shimmyo; Shota Morimoto; Toshiya Tachibana; Tomoya Iseki (Case Reports in Orthopedics)
Background. A talar body fracture is relatively rare. Surgical treatment for the fracture is generally indicated for the displaced fracture types and traditionally performed via open approaches. However, open approaches may not be able to achieve adequate exposure of the talus body owing to the difficulty in achieving reduction and fixation of the fracture. In this case report, we describe a case of talar body fracture treated by hindfoot endoscopic reduction and internal fixation. Case report. A 39-year-old man who was a carpenter complained of right hindfoot pain after he fell from a stepladder during work. Although plain radiographs of the right ankle showed no abnormal findings, noncontrast computed tomography demonstrated a fracture line from the lateral side of the posterior lateral process to the medial side of the talus body. In addition, the fracture line extended to the posterior ankle and subtalar joints, and the bone fragment was slightly displaced. We diagnosed him with the talar body fracture and performed operative treatments using hindfoot endoscopic reduction and internal fixation. At 14 weeks after the operation, he was able to return to work at the preinjury activity level without dysfunction of the ankle nor complications. Conclusion. We reported a case of talar body fracture treated by hindfoot endoscopic reduction and internal fixation. In this case, the hindfoot endoscopic technique provided visualization of the fracture site with less invasiveness and increased safety, which enabled proper reduction and internal fixation of the fracture site. Therefore, the patient was able to return to work at the preinjury activity level at 14 weeks after surgery without dysfunction of the ankle nor complications. This surgical technique may be a useful option for the talar body fracture.